Myths about Menstrual Personal Hygiene among Female Adolescents - Palupi, Tyas Diah; Pristya, Terry Y.R.; Novirsa, Randy (Kesmas, 2020)
Poor personal hygiene during menstruation among adolescents can lead to urinary tract infection, reproductive tract infection, and skin irritation. This studyaimed to determine the relationship between belief in myths and personal hygiene during menstruation. Cross-sectional quantitative study was conductedusing a sample of 119 10th grade female students from Tangerang 13 State Senior High School selected through purposive sampling. Logistic regressionanalysis was used in this study to determine the relationship between myths and personal hygiene after age of menarche, attitude, socioeconomic status,information, and maternal education were controlled. In the bivariate selection, modeling was completed by entering confounding and interaction variablesthen reducing the confounding variables by examining changes in the odds ratio. Results showed that the students who believed the myths were 3.7 timesmore likely to not practice personal hygiene during menstruation compared with those who did not believe the myths after attitude and status socioeconomicstatus were controlled. No interaction was observed between the myths and socioeconomic status.